The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1109/tifs.2017.2675361
|View full text |Cite
|
Sign up to set email alerts
|

NetSpam: A Network-Based Spam Detection Framework for Reviews in Online Social Media

Abstract: Nowadays, a big part of people rely on available content in social media in their decisions (e.g. reviews and feedback on a topic or product). The possibility that anybody can leave a review provide a golden opportunity for spammers to write spam reviews about products and services for different interests. Identifying these spammers and the spam content is a hot topic of research and although a considerable number of studies have been done recently toward this end, but so far the methodologies put forth still … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
80
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(91 citation statements)
references
References 24 publications
2
80
0
Order By: Relevance
“…On the off chance that two connections have a place with a similar kind, the sorts of beginning hub and closure hub of those connections are the same [1].…”
Section: Proposed Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…On the off chance that two connections have a place with a similar kind, the sorts of beginning hub and closure hub of those connections are the same [1].…”
Section: Proposed Methodologymentioning
confidence: 99%
“…It is seen, from the past couple of year's kinfolk who routinely purchase things or organizations from these online social doors settle on decisions in light of the made studies which empowers or cripples them in their assurance of things and organizations. [1] Then again, a lot of writing has been distributed on the systems used to recognize spam and spammers and in addition distinctive sort of investigation on this theme. These systems can be classi fied into various classifications; some utilizing phonetic examples in content, which are for the most part in view of bigram, and unigram [2], others depend on behavioral examples that depend on highlights removed from designs in clients' conduct which are generally metadata based, and even a few procedures utilizing diagrams and chart based calculations and classifiers [3].…”
Section: Introductionmentioning
confidence: 99%
“…The experiments in this section will compare the performance of the TM-DRD and the NFC [24], SpEagle [30], and NetSpam [32] on accuracy indices such as AP and AUC. We verify the impact of the target product review dataset and feature weight calculation on the detection efficiency of TM-DRD and the accuracy of the test results.…”
Section: Comparative Experiments Of Deceptive Review Detectionmentioning
confidence: 99%
“…The datasets YelpChiOP and YelpNYCOP are, respectively, related review datasets on the target product identified by the fusion algorithm based on the anomaly scores proposed in chapter 4 from the original data sets YelpChi and YelpNYC [30]. Next, we will compare the performance of TM-DRD and NFC [24], SpEagle [30], and NetSpam [32] in AP and AUC, respectively, on the above 4 review datasets. We analyze the impact of feature weights on the accuracy of deceptive review detection.…”
Section: Comparative Experiments Of Deceptive Review Detectionmentioning
confidence: 99%
See 1 more Smart Citation